2021
DOI: 10.3389/fpsyt.2021.643556
|View full text |Cite
|
Sign up to set email alerts
|

Early, Chronic, and Acute Cannabis Exposure and Their Relationship With Cognitive and Behavioral Harms

Abstract: Background: Cannabis is the third most consumed drug worldwide. Thus, healthcare providers should be able to identify users who are in need for an intervention. This study aims to explore the relationship of acute, chronic, and early exposure (AE, CE, and EE) to cannabis with cognitive and behavioral harms (CBH), as a first step toward defining risky cannabis use criteria.Methods: Adults living in Spain who used cannabis at least once during the last year answered an online survey about cannabis use and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…These have included panic attacks, paranoia, depression, suicidal ideation, behavioral crises, and even homicidal ideation (Table 2). The psychoactive constituents in marijuana, of which D9-tetrahydrocannabinol (THC) is the main ingredient, disrupt the innate functioning of the endocannabinoid system, which plays a vital role in anxiety, depression, cognition, and many other functions [15][16][17]. The word cannabinoid refers to any chemical substance, regardless of origin or structure, that binds to the cannabinoid receptors of the body and brain [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have included panic attacks, paranoia, depression, suicidal ideation, behavioral crises, and even homicidal ideation (Table 2). The psychoactive constituents in marijuana, of which D9-tetrahydrocannabinol (THC) is the main ingredient, disrupt the innate functioning of the endocannabinoid system, which plays a vital role in anxiety, depression, cognition, and many other functions [15][16][17]. The word cannabinoid refers to any chemical substance, regardless of origin or structure, that binds to the cannabinoid receptors of the body and brain [17].…”
Section: Discussionmentioning
confidence: 99%
“…The psychoactive constituents in marijuana, of which D9-tetrahydrocannabinol (THC) is the main ingredient, disrupt the innate functioning of the endocannabinoid system, which plays a vital role in anxiety, depression, cognition, and many other functions [15][16][17]. The word cannabinoid refers to any chemical substance, regardless of origin or structure, that binds to the cannabinoid receptors of the body and brain [17]. The pathophysiology by which this plant causes an anxiogenic effect in some individuals is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…As quantity of use increases, the odds of having CUD increase, even after controlling for frequency of use and age of onset ( Callaghan et al, 2020 ). Further, past month quantity is significantly positively correlated with dependence symptoms ( López-Pelayo et al, 2021 ). Given difficulty in defining quantity, Zeisser et al (2012) attempted to create a “standard joint” (i.e., 10 puffs on a joint, 5 hits on a bong or pipe, or 0.5 grams of cannabis).…”
Section: Indicators Of Cannabis Problems and Cannabis Use Disordermentioning
confidence: 99%
“…Another factor that may influence the experience of cannabis-related problems and CUD is age of onset (i.e., age of first cannabis use). Though recent work assessing age of onset is limited, several studies found that earlier age of onset (i.e., adolescence) is associated with increased odds of cannabis dependence ( López-Pelayo et al, 2021 ; Richmond-Rakerd, et al, 2016 ) and higher current frequency of use ( Azagba & Asbridge, 2019 ). However, the relation between age of onset and cannabis-related problems may become non-significant when frequency is controlled for ( Rioux et al, 2018 ).…”
Section: Indicators Of Cannabis Problems and Cannabis Use Disordermentioning
confidence: 99%